Effect of Giving Moringa Leaf Infusion (Moringa oleifera) in Triggering Puberty in Peranakan Etawa (PE) Goats - Salmin, Salmin; Sukoco, Hendro; Said, Nur Saidah; Rahmawati, Rahmawati; Awaluddin, Awaluddin; Malewa, Amiruddin; Tantu, Rizal Y. (Jurnal Sain Peternakan Indonesia, 2024)
This study aims to determine the potential benefits of moringa leaf infusion on PE goats' puberty.  The research method used a Randomised Group Design, with five treatments and four groups.  The observed parameters were puberty or time of first estrus, estrus behaviour, estrus quality, onset, and duration.  Analysis in this study used the One-Way ANOVA test followed by Duncan's test to determine the fundamental differences between treatments.  The results of the analysis of variance showed that there is a significant effect between treatments (P <0.05) on puberty.  Treatment P4 (20%) found the fastest puberty time fastest puberty time was found in treatment P4 (20%), which is at the age of PE goats at about 10.25 months, followed by treatment P3 (15%), which is at the age of PE goats at about 10.50 months.  The most extended estrus duration was found in P3 and P4 treatments, 36.50 hours and 36.25 hours, respectively.  This study concludes that moringa leaf infusion can significantly affect puberty or the onset of sexually mature symptoms.  Giving 20% moringa leaf infusion is the maximum dose that can trigger the onset of puberty.  These findings offer hope and optimism for the potential benefits of moringa leaf infusion in managing and developing PE goat farms.